PENGARUH LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS (Studi Kasus Pada Sektor Perusahaan Food and Beverage Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - William, William (Jurnal KIAFE, 2023)
This study aims to examine and analyze the effect of leverage, liquidity and company size on profitability in food and beverage companies for the 2017-2021 period. The data analysis technique used is panel regression analysis. The data used is sourced from the Indonesia Stock Exchange which consists of 35 food and beverage companies. The results of the data analysis show that leverage has a positive and significant effect on profitability, liquidity has a positive and significant effect on profitability and firm size has a negative and significant effect on profitability.